Utilization of roselle (Hibiscus surattensis L.) leaves and swamp taro (Cyrtosperma merkusii) corms in sinigang premix production. - Joaquin, Sharine Orocio
Roselle leaves (Hibiscus surattensis L.) and swamp taro (Cyrtosperma merkusii) corms were utilized in the sinigang premix production. Souring agent from the roselle leaves were extracted by boiling 250 grams roselle leaves in 500 ml water. The optimum boiling time was 15 minutes. Among the three ratios of roselle extract to swamp taro corms: ST1 (1:4), ST2 (1:2) and ST3 (1:1), ST3 was significantly the sourest ratio. The ratio was used as the basis for the production of the sinigang premix. Product from ST3 was subjected to physico-chemical analysis, proximate and microbiological analysis. Physico-chemical properties showed that the water activity of the sinigang premix was 0.69, pH of 3.10 and titratable acidity of the 5.10%. Sinigang premix had 12.71% moisture content, 3.73% ash, 11.98%, 0.14% fat, 0.47% crude fiber and 70.98% carbohydrates. Coliforms and E.coli were not detected in the sinigang premix thus the product was safe for consumption. The Yeast and Mold Count for Run 1 was 106.67cfu/g and in Run2 was 744.33 cfu/g which is lower than the standard of 10,000cfu/g, thus the sample was safe for consumption. Among the three ratios of sinigang premix to fish broth ratio: SP1 (1.5:50), SP2 (2.5:50) and SP3 (3.5:50), SP3 was significantly the most preferred ratio and the sourest ratio. Sinigang soup from the most preferred ratio was rated like moderately. Among the youth group 72% rated the sinigang premix as like moderately to like extremely. Seventy-eight percent (78%) of the adult group rated the sinigang soup like moderately to like extremely.